Strategi Komunikasi Dinas Pemberdayaan Perempuan Dan Perlindungan Anak (DP3A) Kabupaten Bima Dalam Mencegah Kekerasan Dalam Rumah Tangga (KDRT) - Rahmi, Rahmi; Junaidin, Junaidin (CV RIFAINSTITUT, 2024)
Violence frequently occurs in various aspects of society, including within households, which should ideally be places with strong personal relationships. Violence can affect both children and wives. According to fajarmedia.com, the Office of Women's Empowerment, Child Protection, Population Control, and Family Planning reported 23 cases of domestic violence (DV) in 2022. Given the prevalence of DV, the government needs to take steps to reduce these cases. This study focuses on the communication strategy of the Office of Women's Empowerment and Child Protection (DP3A) of Bima Regency in preventing DV. The research employs qualitative methods, collecting data through observation, interviews, and documentation. Data analysis utilizes the POACE theory to understand the stages of DP3A’s communication strategy. In the planning stage, DP3A holds work meetings to draft activity plans, define targets, and set objectives, involving external parties such as the police and MUI. During the preparation stage, field surveys are conducted to understand the geography and culture of the target villages, notifications are sent to these villages, and local PKK members are involved to ensure effective outreach. Implementation involves face-to-face socialization, using media such as PowerPoint, posters, and leaflets to capture the audience’s attention. In the controlling stage, DP3A leadership participates in supervising and monitoring activities to set a good example and make appropriate decisions. The evaluation stage involves collecting and archiving issues or shortcomings from the planning to the evaluation phases for future improvement. All participants are given the opportunity to provide feedback on any deficiencies encountered during the activities.